(-)-Asarinin inhibits mast cells activation as a Src family kinase inhibitor. (April 2020) - Hou, Yajing; Hu, Tian; Wei, Di; Gao, Jiapan; Che, Delu; Wang, Xiangjun; Wang, Cheng; He, Huaizhen
Abstract: As one of the major global health issues, allergic disease represents a considerable burden both on individual patients and public health. (-)-Asarinin (Asa), a lignan isolated from the roots of Asiasari radix, was reported to be associated with anti-allergic effect, but its efficacy and mechanism of action remain unclear. This study investigated the inhibitory effect of Asa on allergic reaction and its mechanism of action. Asa significantly suppressed Ag-sensitized human mast cell line LAD2 calcium mobilization, degranulation, and secretion. It also could reduce OVA-induced local and system anaphylaxis of mice in vivo . Further experiments revealed that Asa inhibit the mast cell activation by preventing the phosphorylation of Src family kinases. Moreover, after the IgE-dependent murine model of allergic rhinitis was treated with Asa, not only the concentration of histamine, total IgE, and IL-4 decreased, but also the inflammatory infiltrates and nasal mucosa incrassation were attenuated significantly. Meanwhile, Asa also inhibited the activation of mast cells induced by Compound48/80 in vivo and in vitro . In conclusion, Asa may serve as a potential novel Src family kinase inhibitor to inhibit IgE-dependent andIgE-independent allergic reaction and treat anaphylactic disease.